Assessment on the Stability and Speciation of Phosphorus in River Sediments - Asmare Atalay; Carol Bronick; Kathleen Baker; Brodie Whitehead (The Global Environmental Engineers, 2015)
Sediments are heterogeneous mixtures of assorted soil separates and organic matter that serve as repositories of many pollutants. This study investigated phosphorus (P) stability in river sediments as controlled by P speciation and environmental conditions, such as temperature (T), dissolved oxygen (DO), redox conditions (Eh), and pH. It attempted to evaluate the experimental conditions under which P could potentially be tied-up in river sediments. Sediment cores samples were collected from James River, in Virginia, U.S.A. near a former dairy farm and analyzed for T, pH, Eh, carbon (C) and pertinent metal ions. Results indicated that high P concentration correlated well with Fe and had non-uniform correlations with clay, Al and Ca, which changed with depth of cores. At low pH, P concentration was higher in anaerobic than aerobic sediments and aluminum (Al) precipitation was highest at low pH, which indicated Al phosphate stability in reduced (anaerobic) conditions. Above pH 7, in aerobic environments, the Minteqa2 speciation model predicted a high stability for Al-OH species. The minerals variscite, vivianite, strengite hydroxyapatite, and two forms of magnesium hydroxide species were predicted to exist in the pH ranges used in this study. Elemental P distribution assessment using Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX) inferred that P could be bound either to C and Al, Fe or Mn depending on their relative abundances.